REREONGAN SERUMPI FOR RURAL DEVELOPMENT IN SITU UDIK VILLAGE BOGOR WEST JAVA - Mujahidin, Endin; Bahagia, Bahagia; Wibowo, Rimun; Mangunjaya, Fachruddin Majeri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The objective of this research to investigate about rareongan sarumpi for rural development in Situ Udik Village Bogor West Java. The research method used qualitative approach. The data are gathred through in-depth interviews, observation, and documentation. The selection of sample as informant exert purposive sampling technique. The result is the leader of village exert non hierarchy and range between society and chief of village. The impact is leader and society are mutual support. The other is community development in Situ Udik village use bottom-up action like rereongan serumpi for society. The resources come from society and give back again result to society. The other is rereongan serumpi conserve gotong royong as cultural. The implementation of rereongan serumpi utilize mutual cooperation (gotong royong). People applicate togetherness, willing to help another people as well as conserve charity for assisting people. Lastly, rereongan serumpi is related to social capital. Individual and other person in inside group have strong social binding as well as society build social connection outside of local people